2013
DOI: 10.5851/kosfa.2013.33.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Goldenrod (Solidago virgaurea) Leaf and Stem Powder on Raw Ground Pork during Chilled Storage

Abstract: The effects of adding goldenrod leaf powder (GLP) and goldenrod stem powder (GSP) (0.1% and 0.5%) to raw ground pork on antioxidant activity were examined. The following six treatment groups were used: Control (without antioxidant), GLP1 (with 0.1% GLP), GLP2 (with 0.5% GLP), GSP1 (with 0.1% GSP), GSP2 (with 0.5% GSP) and AS (with 0.05% ascorbic acid). The chemical compositions, pH values, instrumental color, conjugated diene (CD), free fatty acids (FFA) and thiobarbituric acid-reactive substance (TBARS) value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…As shown in Table 2, the diene values of the two batches significantly increased during processing ( p < .05), and the diene value of batch S was significantly lower than that of batch C ( p < .05). This suggests that lipid oxidation was higher in batch C than in batch S. Kim et al (2013) reported that the formation of conjugated dienes was related to the production of hydroperoxides, and these findings were consistent with the POV results of this study.…”
Section: Resultssupporting
confidence: 91%
“…As shown in Table 2, the diene values of the two batches significantly increased during processing ( p < .05), and the diene value of batch S was significantly lower than that of batch C ( p < .05). This suggests that lipid oxidation was higher in batch C than in batch S. Kim et al (2013) reported that the formation of conjugated dienes was related to the production of hydroperoxides, and these findings were consistent with the POV results of this study.…”
Section: Resultssupporting
confidence: 91%
“…Although a slightly higher antioxidant effect was observed when using pressurized fluid extraction over the ultrasonic extraction method on S. virgaurea L. leaves (94.0% vs. 89.0% inhibition), the difference was not statistically significant [91]. Both leaf and stem powders, as well as extracts obtained from those parts, prevented lipid oxidation when applied on ground pork samples [113,114]. Among 23 herbal species examined for their antioxidant effect in one study, S. vigaurea L. had an average antioxidant activity (in decreasing order, it occupied the 11th position out of 23) [44].…”
Section: Antioxidant Propertiesmentioning
confidence: 87%
“…Although a slightly higher antioxidant effect was observed when using pressurized fluid extraction over the ultrasonic extraction method on S. virgaurea L. leaves (94.0% vs. 89.% inhibition), the difference was not statistically significant [100]. Both leaf and stem powders, as well as extracts obtained from those parts, prevented lipid oxidation when applied on ground pork samples [113,114]. Among 23 herbal species examined for their antioxidant effect in one study, S. vigaurea L. had an average antioxidant activity (in decreasing order, it occupied the 11 th position out of 23) [44].…”
Section: Antioxidant Propertiesmentioning
confidence: 87%